2018
DOI: 10.1186/s13072-018-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed maintenance of transcriptional repression on the inactive X-chromosome in the mouse brain after Xist deletion

Abstract: BackgroundThe long noncoding RNA Xist is critical for initiation and establishment of X-chromosome inactivation during embryogenesis in mammals, but it is unclear whether its continued expression is required for maintaining X-inactivation in vivo.ResultsBy using an inactive X-chromosome-linked MeCP2-GFP reporter, which allowed us to enumerate reactivation events in the mouse brain even when they occur in very few cells, we found that deletion of Xist in the brain after establishment of X-chromosome inactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 33 publications
1
49
1
Order By: Relevance
“…There was also overlap between the regions of XIST required for H3K27me3 and MacroH2A recruitment, and inhibition with GSK343 substantially reduced the recruitment of both to the XIST-coated domain, indicating that MacroH2A recruitment was dependent upon the catalytic activity of PRC2. The discovery of this novel association has yet to be investigated in mouse models, though both have been observed to be lost when Xist is deleted (43,44). At time of writing the mechanisms underlying the connection between PRC2 and MacroH2A during XCI are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There was also overlap between the regions of XIST required for H3K27me3 and MacroH2A recruitment, and inhibition with GSK343 substantially reduced the recruitment of both to the XIST-coated domain, indicating that MacroH2A recruitment was dependent upon the catalytic activity of PRC2. The discovery of this novel association has yet to be investigated in mouse models, though both have been observed to be lost when Xist is deleted (43,44). At time of writing the mechanisms underlying the connection between PRC2 and MacroH2A during XCI are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on maintenance of XCI have revealed several principles by which gene silencing is maintained. The factors and mechanisms that have been involved in maintenance of XCI include Xist [ 45 , 60 , 83 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], DNA methylation [ 83 , 84 , 85 , 88 , 102 , 103 ], histone deacetylation [ 83 ], Polycomb [ 104 , 105 ], H3K9me3 [ 106 ] and macroH2A [ 70 , 107 , 108 ], and likely include additional layers of regulation as well.…”
Section: Maintenance Of XCImentioning
confidence: 99%
“…Erosion of XCI in somatic cells may not manifest itself after several weeks in culture, but could be relevant in aging, although XCR in aging remains largely unclear [ 113 ]. Fourth, several studies have reported examples of partial gene-specific loss of maintenance of XCI upon Xist deletion in the soma [ 97 , 99 ]. Such examples include interesting observations in the immune system where Xist and heterochromatin modifications can show altered patterns in mature naive T and B cells [ 114 , 115 ].…”
Section: Maintenance Of XCImentioning
confidence: 99%
“…We used an epigenetic marker of the inactive X-chromosome, the Histone H3 trimethyl-lysine 27 (H3K27me3) modification, which co-localizes with Xist RNA [39]. The antibody used was rabbit anti-tri-methyl-histone H3 K27-3 m (1:1000, Cell Signaling catalogue #9733S), which has been previously validated and used in mice under similar immunofluorescence conditions [39,102]. The secondary fluorescently labeled antibody was Alexa Fluor 568-conjugated goat anti-rabbit (1:1000; Life Technologies catalogue #A11011).…”
Section: Immunofluorescence and Microscopymentioning
confidence: 99%